Seguimiento de los equipos de atención integral de salud EAIS en la atención extramural. Subcentro de salud Indio Guayas. Periodo. enero - abril 2023 - Manobanda Santillan, Alex Jeovanny (2024)
At the Indio Guayas Health Subcenter, extramural care plays a crucial role in the provision of health services, especially by the Comprehensive Health Care Teams (EAIS). These teams are designed to bring health services directly to communities, working outside of traditional health facilities and ensuring that the guidelines of the Comprehensive Health Care Model with a Family and Intercultural Community Approach (MAIS-CFI) are met. The study the objective was to identify the limitations that influence the Monitoring of EAIS in extramural care at the Indio Guayas Health Subcenter. Period: January-April 2023. Methodology: a quantitative and descriptive approach was used, applying closed questionnaires to 21 professionals who They form 5 EAIS teams and 25 patients considered priority. Data collection followed a cross-sectional design, with direct observation and interviews in the real place of the events. Subsequently, the data were processed and analyzed with IBM SPSS v. 25 software. The results indicated that 88% of the planned extramural activities were fulfilled, recognizing the availability of complete EAIS, as well as resources, as limitations. It is concluded that there is a relatively high compliance with extramural work by the EAIS in the Indio Guayas Health Subcenter, responding within its capabilities and availability to the identified needs. Likewise, to compensate for the deficiencies in monitoring and control, workshops were developed aimed at professionals on topics of planning, management and control of extramural care, recommending their periodic execution to improve the work of the EAIS. Keywords: Extramural care, Comprehensive Health Care Teams (EAIS), Indio Guayas Health Subcenter, Comprehensive Health Care Model with Community, Family, and Intercultural Approach (MAIS-CFI)